Influence of the type of activator combinations on the deflection hardening behavior of geopolymer composites - Nematollahi, B.; Sanjayan, J.; Shaikh, Faiz (RILEM Publications S.A.R.L., 2014)
This paper presents the effects of two different sodium-based (Na-based) and potassium based (K-based) activator combinations on the properties of a recently developed fly ash-based ductile fiber reinforced geopolymer composite (DFRGC) exhibiting deflection hardening and multiple cracking behavior in flexure. Randomly oriented short poly vinyl alcohol (PVA) fibers (2% v/v) were used to reinforce the brittle low calcium (Class F) fly ash-based geopolymer matrix. The Na-based activator combination was composed of 8.0 M NaOH solution (28.6% w/w) and Na2SiO3 solution (71.4% w/w) with a SiO2/Na2O ratio of 2.0; whereas, the K-based activator combination was composed of 8.0 M KOH solution (28.6% w/w) and K2SiO3 solution (71.4% w/w) with a SiO2/K2O ratio of 2.23. The matrix and composite properties of the developed fly ash-based DFRGCs including workability of the fresh matrix, density, compressive and flexural strengths, deflection capacity and composite toughness were evaluated. Experimental results revealed that although the potassium-based DFRGC (DFRGC-K) exhibited superior matrix workability; however, the sodium-based DFRGC (DFRGC-Na) exhibited superior deflection capacity, compressive and flexural strengths with significantly enhanced composite ductility and toughness.